Advances in psoriasis and gut microorganisms with co-metabolites - Zhu, Qiushuang; Wu, Kai; Yang, Qiuhong; Meng, Bo; Niu, Yucun; Zhao, Fenglian (Frontiers in Microbiology, 2023)
This review summarizes the potential role of gut microbes and their metabolites as novel mediators of psoriasis, including their composition and function in disease pathogenesis, progression, and management. Gut microbiota network analysis, colony construction, and in vivo large-scale interaction experiments showed that different degrees of damage and repair in psoriasis, both in animals and humans, involve cross-border homeostasis of the microbial community. Which gut microbiota interactions are present in psoriasis and how they collaborate with immune cells and influence psoriasis development via the gut-skin axis remain incompletely elucidated. In this article, we review the latest information on the unique patterns of gut microbiota and co-metabolites involved in the pathogenesis of psoriasis and attempt to explore microbial-based therapeutic targets derived from mono-and polymicrobial probiotics, fecal microbiota transplantation, pharmacomicrobiomics, and dietary interventions as diagnostic or therapeutic approaches promising to provide new options and long-term management for psoriasis.